Impact of low-level laser therapy on orthodontic pain - Jagła, Sylwia; Bielawska-Victorini, Hanna; Woźniak, Krzysztof (Frontiers in Neurology, 2025)
IntroductionPain is a primary deterrent to patient compliance in orthodontics. While pharmacological options exist, their systemic side effects warrant exploration of non-invasive alternatives. This study introduces Low-Level Laser Therapy (LLLT) as a localized, non-pharmacological intervention and evaluates its efficacy in mitigating pain during the critical initial phase of fixed appliance treatment.MethodsIn this prospective controlled study, 60 patients (aged 14.6–37.1 years) were randomized into an LLLT group (n = 20) and a control group (n = 40). The LLLT group received daily photobiomodulation (670 nm, 4–6 J/cm2) for five consecutive days post-appliance placement. Pain was assessed daily using the Visual Analogue Scale (VAS), Laitinen Scale, and Verbal Rating Scale (VRS). Oral hygiene was evaluated using the Approximal Plaque Index (API).ResultsLLLT significantly reduced pain perception. Pain peaked on day 2 for both groups, but the VAS score was lower in the LLLT group (4.35) than the control group (5.30). By day 4, the difference was highly significant (LLLT: 2.05 vs. Control:3.77; p < 0.0014). Furthermore, the LLLT group demonstrated significantly better oral hygiene, with a lower increase in API scores from T0 to T5 compared to the control group (p < 0.0003).Conclusion and applicationLLLT is an effective and safe modality for reducing acute orthodontic pain. Its localized action, absence of systemic side effects, and positive influence on oral hygiene make it available clinical tool for improving patient comfort and compliance during orthodontic therapy. This study provides strong evidence supporting the integration of LLLT into routine orthodontic practice.